Penerapan Sistem Kendali Fuzzy Logic pada Alat Penyangrai Kopi Tipe Fluidisasi - Arie Nugroho; Abdul Waris; Junaedi Muhidong (Jurnal Agritechno, 2022)
The fluidized coffee roaster is one of roasters which designed to overcome the weaknesses of the conventional roasting method. The purpose of this research is to develop a fluidization type roaster with a Fuzzy Logic control system. The specification of the roaster are roasting chamber dimensions of 65 mm (diameter) and 75 mm (height), a roasting capacity of 40 grams with a roasting time of 300 seconds. A heater with a power of 1,200 W was used as the source of heating energy. The research method was carried out by first, developed a control program and applied to the roaster. Then, a test of functionality and performance was conducted by using Robusta coffee for a temperature set point of 190°C, 200°C, and 210°C. The performance test of control responses resulted in 6.25°C (2,97%) error steady state for 15 seconds. However, this value remains below the tolerance threshold of 5%. The test of the color quality of coffee roasted at 190°C produced 3 groups of coffee colors, namely light brown-yellow, light brown-half-city, and light brown-cinnamon. In the case of roasting temperature of 200°C, it produced 3 color groups, i.e. light brown-city, light brown-full city, and light brown-full city+. For a roasting temperature of 210°C, there were two types of colors, namely dark brown-Vienna and dark brown-Italian. It can be concluded that a fluidized coffee roaster with a fuzzy logic control system was able to produce roast coffee compatible to the target roast profile according to the National Coffee Association (2002), namely light, medium, and dark.